Electrocution in farmed foxes : evaluation from an animal welfare point of view - Korhonen, Hannu. T.; Cizinauskas, Sigitas; Viitmaa, Ranno (dk, 2007)
Abstract The aim was to evaluate at what point consciousness is lost and brain activity ceases in electrically stunned blue foxes (Alopex lagopus), and to establish whether or not there is any return to consciousness after stunning before death. The study was conducted on 15 female blue foxes. All animals were sedated with an intramuscular injection of medetomidine. The results showed that the animal was unconscious immediately after stunning as documented by the absence of all reflexes. The EEG recording showed a status epilepticus pattern in all foxes immediately after stunning, and in none of the animals was a return to normal brain pattern observed. Such a generalised status epilepticus is connected with state of total unconsciousness and leads to ultimately to brain death. All the foxes in our experiment had respiratory arrest and heart fibrillation after stunning. The heart changes were irreversible in all cases and most probably contributed heavily to the death of the brain after stunning, as the fibrillating heart is not able to provide the necessary blood flow to the brain and other organs. This leads to failure of multiple organ systems and inevitable death. Rapid disappearance of the BAER after stunning indicates brainstem affection and death. Magnetic resonance imaging examination and histopathological examination of the brain revealed no severe changes to the brains of any of the foxes, indicating that stunning mainly affects the function of the brain without distorting the anatomy of the brain. In conclusion, electrical stunning produces an immediate and irreversible state of unconsciousness and therefore is a humane way of euthanasia of farmed foxes.
Keywords: Ko; turkiseläimet; etiikka; furbearing animals; ethics